Aequorivita iocasae sp. nov., a halophilic bacterium isolated from sediment collected at a cold seep field in the South China Sea. Issue 2 (8th February 2022) - Zhang, Huan; Wang, Hao; Cao, Lei; Chen, Hao; Zhong, Zhaoshan; Wang, Minxiao; Lian, Chao; Liu, Rui; Zhou, Li; Li, Chaolun
Abstract : A moderately halophilic bacterium, designated strain KX20305 T, was isolated from sediment collected from a cold seep field in the South China Sea. Cells of strain KX20305 T were Gram-stain-negative, rod-shaped, non-motile, facultatively anaerobic, oxidase- and catalase-positive, and grew optimally at 25–30 °C, pH 6.0–8.0 and with 3–6 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences showed that strain KX20305 T grouped with members of the genus Aequorivita, including Aequorivita aquimaris D-24 T (98.3 % sequence similarity), Aequorivita vladivostokensis KMM 3516 T (98.1 %) and Aequorivita echinoideorum CC-CZW007 T (97.5 %). Genome sequencing of strain KX20305 T revealed a genome size of 3.35 Mb and a DNA G+C content of 38.71 mol%. Genomic average nucleotide identity (orthoANI) values of strain KX20305 T with A. aquimaris D-24 T, A. vladivostokensis KMM 3516 T and A. echinoideorum JCM 30378 T were 83.8, 81.7 and 75.4 %, respectively, while in silico DNA–DNA hybridization (GGDC) values for strain KX20305 T with these strains were 27.2, 25.0 and 19.6 %, respectively. The major fatty acids of strain KX20305 T were iso-C15 : 0, iso-C17 : 0 3-OH and 10-methyl C16 : 0 /iso-C17 : 1  ω 9 c . The predominant respiratory quinone was menaquinone-6 (MK-6). The polar lipids mainly comprised phosphatidylethanolamine, two unidentified aminolipids and two unidentified lipids. Based on comparative analysis of phylogenetic, phylogenomic, phenotypic and chemotaxonomic characteristics, strain KX20305 T represents a novel species of the genus Aequorivita, for which the name Aequorivita iocasae sp. nov. is proposed. The type strain is KX20305 T (=KCTC 82699 T =MCCC 1K06238 T =JCM 34635 T ).